Modernes pietà - Aurel Rotival (Images Re-Vues, 2018)
This article proposes to study a singular and paradoxical community of figures identified in three films created in the political and revolutionary context of the sixties : in Children Out of Tune (P. Garrel, 1964), Acéphale (P. Deval, 1968), and Gods of the Plague (R. W. Fassbinder, 1970), survives the figurative pattern, inherited from christian painting, of a pietà. The first step is to consider the dialectical potential of this exemplary pathetic gesture, and to understand how it can also serve as a starting point for the expression of a critical and political position. The question then arises of the period of an anthropological crisis, especially described by P. P. Pasolini and E. De Martino, which led to the reinvestment of these religious symbols and the role they thus play as medium of a memorial safeguard and a spiritual shelter. Finally, it is a question of considering the necessary political dimension that the religious pathos may bear when it reappears at times when revolution, emancipation and salvation must be thought together.